2013
DOI: 10.1074/jbc.m112.382473
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Dimerization of the Growth Hormone Secretagogue Receptor (GHS-R1a) Attenuates Ghrelin-mediated Signaling

Abstract: Background:The ghrelin receptor (GHS-R1a) has multiple biological functionalities, including the regulation of appetite and hedonic food intake. Results: A novel GHS-R1a/5-HT 2C heterodimer was identified, in addition to GHS-R1a/D 1 and GHS-R1a/MC 3 . Conclusion: Promiscuous GHS-R1a receptor heterodimerization attenuates downstream signaling and affects trafficking depending on dimer partner. Significance: The existence of multiple GHS-R1a heterodimers has important consequences for the future development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(174 citation statements)
references
References 70 publications
5
158
0
11
Order By: Relevance
“…Recently, a novel heterodimer between the ghrelin receptor (GHS-R1A) and the unedited 5-HT2C receptor has been identified. Dimerization of GHS-R1A receptor with the unedited 5-HT2C receptor reduced the GHS-1RA receptor-mediated calcium influx [199].…”
Section: Brain Mechanisms Of Serotonergic Satietymentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, a novel heterodimer between the ghrelin receptor (GHS-R1A) and the unedited 5-HT2C receptor has been identified. Dimerization of GHS-R1A receptor with the unedited 5-HT2C receptor reduced the GHS-1RA receptor-mediated calcium influx [199].…”
Section: Brain Mechanisms Of Serotonergic Satietymentioning
confidence: 93%
“…Another approach to 5-HT2C receptor pharmacology in the context of obesity could arise from the dimerization of this G-protein coupled receptor as demonstrated with the ghrelin receptor [199,354]. Although this concept of warrants further research, dimerization of the 5-HT2C receptor increases the pharmacological diversity of this receptor and thus the development of new drugs.…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with our previous study and confirms the 5-HT2C receptor-mediated attenuation of GHS-R1a receptor signalling, which concurs the interaction between the two receptors 27 . Previously, it has been shown that the GHS-R1a receptor dimerizes with the dopamine D1 receptor leading to an enhanced dopamine induced c-AMP accumulation 24 and an attenuation of GHS-R1a-mediated calcium signalling 27 . This may suggest a dimer-induced switch in GHS-R1a receptor G-protein coupling from Gαq to Gαs, which has been previously suggested for neuronal GHS-R1a receptors expressed in neuropeptide Y (NPY) cells of the arcuate nucleus of the hypothalamus 69 .…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, the GHS-R1a receptor has also been shown to heterodimerize with other GPCRs involved in appetite regulation and food reward (for review see 19 ), including its truncated splice variant, the GHS-R1b receptor 18,[20][21][22] , the melanocortin 3 receptor (MC3) and the dopamine receptors (D1 and D2) [23][24][25][26][27] . Moreover, our lab has demonstrated compelling evidence for a functional interaction between the GHS-R1a and the 5-HT2C receptor 27 .…”
Section: Introductionmentioning
confidence: 99%